Double intussusception in a child - The triple-circle sign - Kazez, A; Ozel, SK; Kocakoc, E; Kiris, A (Wiley, 2004)
Intussusception is a common surgical problem in childhood and is defined as a prolapse of a part of the intestine into the lumen of an immediately adjoining part.(1-3) Double intussusception (DI) in children is a very rare entity, and its diagnosis is made during surgical interventions. In classic cases, the displacement of 1 segment of bowel is defined, whereas, very rarely, 2 separate segments can prolapse into the same distal segment, giving rise to DI.(4,5) To our knowledge, 3 DI cases in the pediatric age group have been reported in the English literature to date.(4,5) A target sign is a typical finding of classic intussusception on sonography and computed tomography (CT).(6,7) The sonographic and tomographic findings in an 8-year-old patient with DI were evaluated retrospectively, and the triple-circle sign was noticed, which was different from the classic target sign and which, to our knowledge, has not been defined previously.
Keywords: Diagnosis